Pathological pericyte expansion and impaired endothelial cell-pericyte communication in endothelial Rbpj deficient brain arteriovenous malformation - Selhorst, Samantha; Nakisli, Sera; Kandalai, Shruthi; Adhicary, Subhodip; Nielsen, Corinne M. (Frontiers in Human Neuroscience, 2022)
Pericytes, like vascular smooth muscle cells, are perivascular cells closely associated with blood vessels throughout the body. Pericytes are necessary for vascular development and homeostasis, with particularly critical roles in the brain, where they are involved in regulating cerebral blood flow and establishing the blood-brain barrier. A role for pericytes during neurovascular disease pathogenesis is less clear – while some studies associate decreased pericyte coverage with select neurovascular diseases, others suggest increased pericyte infiltration in response to hypoxia or traumatic brain injury. Here, we used an endothelial loss-of-function Recombination signal binding protein for immunoglobulin kappa J region (Rbpj)/Notch mediated mouse model of brain arteriovenous malformation (AVM) to investigate effects on pericytes during neurovascular disease pathogenesis. We tested the hypothesis that pericyte expansion, via morphological changes, and Platelet-derived growth factor B/Platelet-derived growth factor receptor β (Pdgf-B/Pdgfrβ)-dependent endothelial cell-pericyte communication are affected, during the pathogenesis of Rbpj mediated brain AVM in mice. Our data show that pericyte coverage of vascular endothelium expanded pathologically, to maintain coverage of vascular abnormalities in brain and retina, following endothelial deletion of Rbpj. In Rbpj-mutant brain, pericyte expansion was likely attributed to cytoplasmic process extension and not to increased pericyte proliferation. Despite expanding overall area of vessel coverage, pericytes from Rbpj-mutant brains showed decreased expression of Pdgfrβ, Neural (N)-cadherin, and cluster of differentiation (CD)146, as compared to controls, which likely affected Pdgf-B/Pdgfrβ-dependent communication and appositional associations between endothelial cells and pericytes in Rbpj-mutant brain microvessels. By contrast, and perhaps by compensatory mechanism, endothelial cells showed increased expression of N-cadherin. Our data identify cellular and molecular effects on brain pericytes, following endothelial deletion of Rbpj, and suggest pericytes as potential therapeutic targets for Rbpj/Notch related brain AVM.